The Concept of Maslahah Mursalah and Its Implementation in Sustainable Sharia Financial Literacy in the Modern Era - Verawati, Heni; Zathu Restie Utamie (Al-Mashrof: Islamic Banking and Finance, 2025)
Maslahah Mursalah is one of the important concepts in Islamic law that focuses on the general welfare of humanity without any specific evidence governing it. This concept serves as a relevant foundation in addressing contemporary challenges, including sustainable Sharia-based financial literacy in the modern era. This article aims to examine the concept of Maslahah Mursalah, as well as its implementation in enhancing Sharia-compliant financial literacy oriented towards sustainability. Using a qualitative research method based on literature review, this article analyzes how the principles of maslahah can be applied to support financial management that is not only in accordance with Islamic law but also has a positive impact on economic, social, and environmental sustainability. The study results indicate that Maslahah Mursalah can serve as a strategic framework in promoting inclusivity and sustainability in Islamic finance. By considering universal values such as justice, balance, and utility, Sharia financial literacy based on Maslahah Mursalah can meet the needs of modern society while also supporting the achievement of Sustainable Development Goals (SDGs). This article recommends synergy between Islamic financial institutions, academics, and the government in enhancing maslahah-based financial literacy to strengthen the Islamic economic ecosystem in the modern era.   Keywords: Maslahah Mursalah, Financial Literacy, Sustainable Finance, Sharia, Modern Era.